Hukum Menikahi Kakak/Adik Ipar - Muhammad Idris (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
This paper will elaborate about legal married of brother/sister in law. The problem are what the legal Islamic law in marrying brother/sister in law namely to discuss various sources about marriage in Islam started definition of marriage, the legal basis, and discussion about mahram and not mahram. Discussion about the problem of marriage generally become interesting topic because the implementation of marriage itself in society cause various problem which yet or has been determined by Islamic law. However, muslim society in Indonesia widely do not know about legal married itself whereas they have committed to marriages. Marriages is bonding the inner and outer between man and women as husband and wife to have family with opposite sex happy and eternal namely family sakinah, mawaddah warahmah based on syari’at Islam which is one main principles of life in intercommunication or perfect society. So it can be understood that marriage will be considered legal if it is done according to marriage law for religion and belief and noted by authority institution based applicable laws. The law marry ex husband/wife of brother/sister is allowed because they are temporary mahram not eternal mahram so if there is a divorce either because divorce in court or because divorce by death, so the status become legal to be married especially after long time.